2016
DOI: 10.1186/s12885-016-2903-z
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-associated in colon cancer-1 and aldehyde dehydrogenase 1 are metastatic and prognostic biomarker for non-small cell lung cancer

Abstract: BackgroundTumor recurrence and metastasis are the most common reason for treatment failure. Metastasis-associate in colon cancer-1 (MACC1) has been identified as a metastatic and prognostic biomarker for colorectal cancer and other solid tumors. Aldehyde dehydrogenase 1 (ALDH1), a marker of cancer stem cells, is also associated with metastasis and poor prognosis in many tumors. However, the prognostic value of either MACC1 or ALDH1 in non-small cell lung cancer (NSCLC) is unclear. In this study, we explored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…Our study proves that MACC1 is elevated in patients with lung adenocarcinoma and that MACC1 knockdown significantly attenuates proliferation capability, induces G0/ G1 phase arrest and stimulates cell apoptosis in vitro in lung adenocarcinoma cells by regulating the β-catenin pathway. MACC1 elevated expression and prognostic value have been demonstrated in multiple tumors [6,10,[14][15][16][17][18], and our results of tissue samples and database search coincide with the well-documented NSCLC data provided by Wang et al and Zhou et al [10,11]. Numerous studies on the correlation between MACC1 expression and clinical pathological parameters indicate its prognostic value in a variety of cancers [5,8,19].…”
Section: Macc1 Knockdown Effects On Cell Proliferation Cell Cycle Ansupporting
confidence: 87%
See 1 more Smart Citation
“…Our study proves that MACC1 is elevated in patients with lung adenocarcinoma and that MACC1 knockdown significantly attenuates proliferation capability, induces G0/ G1 phase arrest and stimulates cell apoptosis in vitro in lung adenocarcinoma cells by regulating the β-catenin pathway. MACC1 elevated expression and prognostic value have been demonstrated in multiple tumors [6,10,[14][15][16][17][18], and our results of tissue samples and database search coincide with the well-documented NSCLC data provided by Wang et al and Zhou et al [10,11]. Numerous studies on the correlation between MACC1 expression and clinical pathological parameters indicate its prognostic value in a variety of cancers [5,8,19].…”
Section: Macc1 Knockdown Effects On Cell Proliferation Cell Cycle Ansupporting
confidence: 87%
“…However, MACC1 knockdown can inhibit cell proliferation, colony formation, invasion, arrest the cell cycle in the G0/G1 phase and induce cell apoptosis in human osteosarcoma [9]. While it has been reported that high MACC1 levels predict worse prognosis in NSCLC patients [10][11][12], its function and underlying molecular mechanisms remain unclear.…”
mentioning
confidence: 99%
“…MACC1 is also reported to not only promote tumor cell proliferation, invasion, and dissemination by inducing epithelial-mesenchymal transition (EMT) in vitro [ 5 , 6 ] but also to induce tumor cell growth, invasion, and metastasis in vivo [ 3 , 7 ]. It has been demonstrated that MACC1 should be defined as a prognostic and metastatic biomarker for various cancers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…CSCs have the characteristics of self-renewal, proliferation, invasiveness, and metastasis. They are responsible for cancer initiation and natural resistance to therapy [ 8 – 12 ]. CD44 is not only a common biomarker of CSCs in cancers, such as colorectal cancer, lung cancer, and glioblastoma [ 13 – 15 ], but also a receptor of hyaluronan.…”
Section: Introductionmentioning
confidence: 99%
“…The ALDH1 family of enzymes (namely ALDH1A1, ALDH1A2 and ALDH1A3) is a cytosolic detoxifying enzyme responsible for the oxidation of (retin)aldehydes into retinoids [5]. It has been widely used to isolate cancer stem cells [6].…”
Section: Introductionmentioning
confidence: 99%